ADVANCEMENTS IN GREEN CHEMISTRY: DEVELOPING SUSTAINABLE CATALYSTS FOR ECO-FRIENDLY INDUSTRIAL PROCESSES - Iqbal, Mochammad (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2024)
Green chemistry has become an important technique for solving environmental problems in the chemical industry, with an aim of developing sustainable catalysts for eco-friendly industrial processes. This review considers recent advancements in green chemistry particularly regarding development and application of sustainable catalysts. The study examines different varieties of sustainable catalysts from renewable materials, mild and energy-saving operational conditions as well as minimizing waste and enhancing recyclability. Furthermore, it also discusses key industrial applications like ammonia and hydrogen peroxide production using more sustainable processes. In addition, there is a growing embrace of green chemistry principles across other areas such as fine chemicals and pharmaceuticals. Nonetheless, some significant challenges still exist including need for more generalized and scalable means of discovery and optimization of catalysts. The paper underscores that bridging academia and industry gaps is crucial to successfully adopting green chemistry research in industrial contexts. For instance, accelerated discovery and optimization of sustainable catalysts depend heavily on advancements in data-driven strategies such as high-throughput experimentation as well as computational modeling.